Countermovement jump standards in rugby league: what is a "good" performance? - McMahon, J. J.; Lake, J. P.; Dos' Santos, T.; Jones, P. A.; Thomasson, M. L.; Comfort, P. (The Journal of Strength and Conditioning Research, 2022)
The countermovement jump (CMJ) is considered an important test in rugby league, and the force platform is the recommended tool for assessing CMJ performance in this cohort. Because of inconsistent methods applied across previous studies, there is currently a lack of understanding of what constitutes a "good" CMJ performance, with respect to the typical CMJ metrics that are reported for rugby league players. The purpose of this study was, therefore, to produce a scale of reference values for the jump height (JH), reactive strength index modified (RSImod), and mean (PPmean) and peak (PPpeak) propulsion power (relative to body mass) for top-level senior rugby league players competing in the global "forward" and "back" positional groups. One hundred four players (55 forwards and 49 backs) from the top 2 tiers of English rugby league performed 3 CMJs on a force platform at the beginning of pre-season training. The JH, RSImod, PPmean, and PPpeak were calculated using criterion methods, and a scale of norm-referenced values (percentiles) was produced for each positional group. The backs outperformed the forwards for each CMJ metric reported, thus supporting the production of position-specific norm-referenced values. When each positional group was separated into quartile subgroups, the respective JH, RSImod, PPmean, and PPpeak values were mostly largely and significantly different both within and between positions. The presented scale of reference values can, therefore, be used to determine the performance standards of rugby league forwards and backs with respect to the most commonly reported CMJ-derived variables for this cohort.